The expression of Toll-like receptors-2 and-4 by human crypt intestinal epithelial cells, intestinal myofibroblasts and putative intestinal stem cells in inflammatory bowel disease - Brown, Matthew (2012)
Host-microbial interactions are of major importance in the pathogenesis of inflammatory bowel disease (IBD). Toll-like receptors (TLR) are pattern recognition receptors which recognise conserved molecular patterns derived from micro-organisms. Crypt intestinal epithelial cells (IEC) were isolated form mucosal specimens of healthy controls and patients with IBD (ulcerative colitis, UC, and Crohn's disease). A population of IEC enriched for intestinal stem cells (ISC) were identified using Hoechst dye exclusion and by their adherence to cultured primary intestinal myofibroblast cell monolayers.